Pembangunan Desa Wisata Gerabah Kasongan di Desa Bangunjiwo, Kecamatan Kasihan, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Pratama, Yohanes Mario (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Bangunjiwo Village, Kapanewon Kasihan, Bantul Regency has a very famous area as a center for pottery, namely in the Kasongan area. The Covid-19 pandemic has had a significant impact due to a decrease in the number of tourists. To assist the recovery and development of village potential, this community service program aims to develop the potential of tourism villages. This program is carried out using secondary data to find the potential that exists in Bangunjiwo Village that can be developed. Based on these data, it is then learned what needs to be developed in Bangunjiwo Village. The development of tourism village potential is carried out by rearranging places that might be used as tourist village centers by redesigning tourist areas with interesting concepts such as information rooms, rest areas, restaurants, and workshop spaces. This work program is expected to be able to attract tourists so that it can advance Bangunjiwo Village and of course requires parties from village officials, villagers, and the regional tourism office.